Preparation and Evaluation of Combined Detection of Norovirus GI and GII: An Innovative Fluorescent Particles Test Strip. (25th February 2018) - Zhang, Lifang; Peng, Yanxia; Jiang, Na; Shi, Lei; Lin, Jieping; Wu, Ping; Pan, Qingjun
Abstract : This study was designed to prepare and evaluate the sensitivity and specificity of a Norovirus GI and GII fluorescent particles combined detection test strip method. Using selected chromatographic materials and antibodies specific to Norovirus GI and GII, the Norovirus GI and GII fluorescent particles combined detection test strip (tested method) was prepared as a conventional double antibody sandwich. The samples assayed included cultured rotavirus and 465 specimens from patients with symptoms of gastrointestinal infection. Norovirus was detected using the tested method and a reference method (CerTest Norovirus GI-GII test card). The results indicated that the sensitivity of the tested method was 4 (for GI detection) or 8 times (for GII detection) greater than the reference method. Neither of the two methods cross-reacted with rotavirus and so on. For specimens, 29 were found to be negative by the reference method and positive by the tested method, and 8 were found to be negative by the tested method and positive by the reference method. Furthermore, a retesting of these samples by qPCR showed that 28 of the 29 were positive, and 3 of the 8 were positive. In summary, the Norovirus GI and GII fluorescent particles combined detection test strip was successfully prepared and had good detection performance.